(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article discusses the analytical and visual capabilities of the Microsoft Excel program, in particular, methods for analyzing quality characteristics and displaying them in graphical form. The article scientifically analyzes the methods of processing data based on quality indicators and visualizing them using dynamic tables and diagrams. The use of the Excel program in the fields of quality management, production, education and service is also substantiated through practical examples.